Self-dispersing nano silicon dioxide particle for cement-based material and preparation method of self-dispersing nano silicon dioxide particle
Through the chemical adsorption and steric hindrance of alkylsilane and nanosilia, the problem of poor dispersion of nanosilia in cement-based materials is solved, which improves the early and later mechanical properties of the material and reduces the preparation cost.
Patent Information
- Application Number
- CN202411424256.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-07
AI Technical Summary
Nanosilicon dioxide is prone to agglomeration in cement-based materials and has poor dispersion, resulting in an improvement in early compressive and flexural strength but a decrease in mechanical properties in later stages, and a high specific surface area leads to a large amount of water demand and a decrease in working performance.
After mixing alkyl silane with water and heating, nanosilia is added, and it is dispersed by chemical adsorption. The carbon chain of alkyl silane provides steric hindrance and hydrophobicity, and the amount of alkyl silane is used to limit the amount of alkyl silane to avoid hydration of cement. Influence.
The stable dispersion of nano silica in cement-based materials is achieved, which improves the early and later mechanical properties of the material, reduces the adverse effects on cement-based materials, and reduces the preparation cost.
Smart Images

Figure CN119263677A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building materials, and in particular relates to self-dispersed nano silicon dioxide particles for cement-based materials and a preparation method thereof. Background Art
[0002] Nano-silicon dioxide is a commonly used nano-modified material for cement-based materials. Its small size makes it have a significant filling effect, which improves the compactness of the microstructure of cement-based materials. In addition, nano-silicon dioxide can also react with Ca(OH) 2 A volcanic ash reaction occurs, further filling the pores and increasing the density of cement-based materials. At the same time, the aggregate / paste interface and fiber / paste interface are also strengthened. The early compressive and flexural strengths of cement-based materials added with nano-silicon dioxide are improved, and the later mechanical properties of cement-based materials are also improved when the dosage is appropriate. However, the high surface energy brought by the high specific surface area of nano-silicon dioxide makes it easy to agglomerate. Although it can be dispersed by surfactants and ultrasonic methods, its dispersion is poor when the dosage is large, and the reinforcement effect becomes worse. In addition, the high specific surface area also causes a large water demand, increases the yield stress and plastic viscosity of the fresh cement-based material paste, and greatly reduces the working performance.
[0003] Therefore, it is necessary to provide an improved technical solution to address the above-mentioned deficiencies in the prior art. Summary of the invention
[0004] The purpose of the present invention is to provide a self-dispersing nano-silicon dioxide particle for cement-based materials and a preparation method thereof, so as to help solve or alleviate the problem of easy agglomeration and poor dispersibility of nano-silicon dioxide when applied to cement-based materials in the prior art.
[0005] In order to achieve the above-mentioned object, the present invention provides the following technical scheme: a method for preparing self-dispersing nano-silica particles for cement-based materials, comprising the following steps: (1) mixing alkyl silane and water, stirring and heating; (2) when the temperature is heated to above 80°C, adding nano-silica and continuing to stir; (3) after the stirring is completed, separating the solid and the liquid, and drying to obtain the self-dispersing nano-silica particles for cement-based materials.
[0006] Preferably, the mass ratio of the alkylsilane to the nano-silicon dioxide is (0.5-1.5):100.
[0007] Preferably, the silane is at least one of propyltrimethoxysilane, propyltriethoxysilane, dodecyltrimethoxysilane and dodecyltriethoxysilane.
[0008] Preferably, the alkylsilane includes dodecyltrimethoxysilane and / or dodecyltriethoxysilane. After adding the nano-silica in step (2), stirring is continued for 2 hours before stopping heating and stirring.
[0009] Preferably, the alkyl silane is propyltrimethoxysilane and / or propyltriethoxysilane. After adding the nano-silica in step (2), stirring is continued for 30 minutes before stopping heating or stirring.
[0010] Preferably, the average size of the nano-silicon dioxide is less than 100 nm. 2 The content is greater than 99%; the mass ratio of the nano silicon dioxide to water is (5-20):100.
[0011] The present invention also provides a self-dispersing nano-silicon dioxide particle for cement-based materials, which adopts the following technical scheme: the self-dispersing nano-silicon dioxide particle for cement-based materials is prepared by the method as described above.
[0012] The present invention also proposes a cement-based material, which adopts the following technical solution: a cement-based material, wherein the components of the cement-based material include the self-dispersed nano-silicon dioxide particles for cement-based materials as described above.
[0013] Preferably, the cement-based material is cement mortar, which comprises the following components in parts by weight: 140-160 parts of cement, 140-160 parts of fly ash, 850-950 parts of river sand, 1-5 parts of the self-dispersing nano-silicon dioxide particles for cement-based materials, 80-150 parts of water and 1.2-1.8 parts of water reducer.
[0014] Beneficial effects:
[0015] (1) In the method for preparing self-dispersible nano-silica particles for cement-based materials of the present invention, the hydroxyl groups generated by the hydrolysis of the alkylsilane can react with the hydroxyl groups on the surface of the nano-silica by condensation reaction (such as Figure 1-2 ), and thus adsorbed to the surface of nano-silica particles by chemical adsorption. Its adsorption force is more stable than the physical adsorption of surfactants, so the dispersion effect is more stable. In addition, the alkylsilane carbon chain has a steric hindrance, so its dispersion effect is good.
[0016] (2) The self-dispersing nano-silica particles for cement-based materials of the present invention can disperse the nano-silica particles due to the steric hindrance of the carbon chain of alkylsilane, and at the same time, the hydrophobicity of alkylsilane can reduce the moisture adsorbed on the surface of the nano-silica particles, thereby greatly reducing the influence of the nano-silica particles on the working performance of the cement-based materials.
[0017] (3) In the method for preparing self-dispersible nano-silica particles for cement-based materials of the present invention, by selecting alkyl silane as a modifier, it is helpful to avoid the retarding effect of active groups on the silane carbon chain, such as amino, epoxy, acyloxy, etc., on cement hydration.
[0018] (4) In the method for preparing self-dispersible nano-silica particles for cement-based materials of the present invention, by limiting the amount of alkyl silane to 0.5-1.5%, it is helpful to reduce the excessive adsorption of alkyl silane, and its hydrophobicity has a great influence on the reaction between nano-silica and Ca(OH) 2 The inhibition of the pozzolanic reaction between the two groups avoids the decrease in the strength of cement-based materials after 28 days. At the same time, it avoids the problem of small adsorption of alkyl silane and poor self-dispersion effect.
[0019] (5) The method for preparing self-dispersed nano-silica particles for cement-based materials of the present invention can directly adsorb alkyl silane onto the surface of nano-silica particles, and has a simple preparation process, a small adsorption amount, and a low cost, and is easier to promote and apply.
[0020] (6) In the method for preparing self-dispersible nano-silica particles for cement-based materials of the present invention, the solution is heated to above 80° C. to accelerate the hydrolysis and adsorption process of silane and shorten the time required for preparing the self-dispersible nano-silica particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. Among them:
[0022] Figure 1 Schematic diagram of the reaction of alkylsilane hydrolysis; wherein M is a methyl group or an ethyl group, and R is an alkyl carbon chain;
[0023] Figure 2 The schematic diagram of chemical adsorption of alkyl silane and nano-silicon dioxide, wherein R is an alkyl carbon chain;
[0024] Figure 3 The figure is a test result diagram of the fluidity of cement mortar of Examples 9-10, Comparative Example 1 and Comparative Example 7;
[0025] Figure 4 The graph is a test result of the compressive strength of the cement mortar of Example 9, Comparative Example 1 and Comparative Example 7;
[0026] Figure 5 This is a graph showing the test results of the compressive strength of the cement mortar of Example 10, Comparative Example 1 and Comparative Example 7. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. All other embodiments obtained by ordinary technicians in this field based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0028] The present invention will be described in detail below in conjunction with embodiments. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.
[0029] The present invention aims at the problem that nano silicon dioxide is easy to agglomerate and has poor dispersibility when currently used in cement-based materials, and provides a self-dispersing nano silicon dioxide particle for cement-based materials, a preparation method and an application thereof.
[0030] The method for preparing self-dispersing nano-silica particles for cement-based materials according to an embodiment of the present invention comprises the following steps: (1) mixing alkyl silane with water, stirring and heating; (2) when the temperature is heated to above 80°C, adding nano-silica and continuing stirring; (3) after the stirring is completed, solid-liquid separation and drying are performed to obtain self-dispersing nano-silica particles for cement-based materials. In particular, heating to above 80°C (preferably, heating to 80-95°C; for example, 80°C, 85°C, 90°C or 95°C) in step (2) helps to accelerate the hydrolysis and adsorption process of silane and shorten the time required for preparing the self-dispersing nano-silica particles.
[0031] The method for preparing self-dispersible nano-silica particles for cement-based materials of the present invention comprises mixing, stirring and heating alkyl silane with water, which helps to hydrolyze the alkyl silane to generate hydroxyl groups, which can then react with the hydroxyl groups on the surface of the nano-silica to form condensation groups (such as Figure 1-2 As shown in the figure, alkyl silane can be adsorbed onto the surface of nano-silica particles by chemical adsorption (chemical adsorption is more stable than physical adsorption), which helps to make the dispersion effect of nano-silica particles more stable; in addition, the carbon chain of alkyl silane has a steric hindrance and a good dispersion effect; the hydrophobicity of alkyl silane also helps to reduce the moisture adsorbed on the surface of nano-silica particles, thereby greatly reducing the impact of nano-silica particles on the working performance of cement-based materials; further, compared with other silanes, alkyl silane does not have active groups such as amino, epoxy, and acyloxy groups, which helps to reduce or avoid the retarding effect of active groups on cement hydration.
[0032] The method for preparing self-dispersed nano silicon dioxide particles for cement-based materials of the present invention can directly adsorb alkyl silane onto the surface of nano silicon dioxide particles, has simple preparation process, small adsorption amount, low cost, and is easier to promote and apply.
[0033] In a preferred embodiment of the method for preparing self-dispersed nano-silica particles for cement-based materials of the present invention, the mass ratio of alkylsilane to nano-silica is (0.5-1.5):100 (for example, 0.5:100, 0.7:100, 0.9:100, 1.1:100, 1.3:100 or 1.5:100). In particular, by limiting the amount of alkylsilane to less than 1.5%, it is helpful to reduce the hydrophobicity of alkylsilane on the nano-silica and Ca(OH) in cement-based materials. 2 The inhibition of the pozzolanic reaction between the two avoids the decrease in the 28-day strength of the cement-based material; if the amount of alkyl silane used is too small, its effect on improving the dispersibility of nano-silica is poor.
[0034] In a preferred embodiment of the method for preparing self-dispersed nano-silica particles for cement-based materials of the present invention, the silane is at least one of propyltrimethoxysilane, propyltriethoxysilane, dodecyltrimethoxysilane and dodecyltriethoxysilane.
[0035] In a preferred embodiment of the method for preparing self-dispersed nano-silica particles for cement-based materials of the present invention, the alkyl silane includes dodecyltrimethoxysilane or dodecyltriethoxysilane, and after adding the nano-silica in step (2), stirring is continued for 2 hours before stopping heating and stirring (to help ensure that the alkyl silane is substantially completely adsorbed).
[0036] In a preferred embodiment of the method for preparing self-dispersed nano-silica particles for cement-based materials of the present invention, the alkyl silane is propyltrimethoxysilane and / or propyltriethoxysilane, and after adding the nano-silica in step (2), stirring is continued for 30 minutes before stopping heating or stirring (to help ensure that the alkyl silane is substantially completely adsorbed).
[0037] In a preferred embodiment of the method for preparing self-dispersed nano-silicon dioxide particles for cement-based materials of the present invention, the average size of the nano-silicon dioxide is less than 100 nm, and the SiO 2 The content is greater than 99%; the mass ratio of nano-silicon dioxide to water is (5-20):100 (for example, 5:100, 8:100, 12:100, 15:100, 18:100 or 20:100).
[0038] The present invention also provides a self-dispersing nano-silicon dioxide particle for cement-based materials. The self-dispersing nano-silicon dioxide particle for cement-based materials in the embodiment of the present invention is prepared by the method described above.
[0039] The present invention further provides a cement-based material. The components of the cement-based material in the embodiment of the present invention include the self-dispersed nano-silicon dioxide particles for cement-based materials as described above.
[0040] In a preferred embodiment of the cement-based material of the present invention, the cement-based material is cement mortar, and the cement mortar includes the following components in parts by weight: 140-160 parts of cement (for example, 140 parts, 145 parts, 150 parts, 150 parts or 160 parts), 140-160 parts of fly ash (for example, 140 parts, 145 parts, 150 parts, 150 parts or 160 parts), 850-950 parts of river sand (for example, 850 parts, 870 parts, 890 parts, 920 parts or 950 parts), 1-5 parts of self-dispersed nano-silicon dioxide particles for cement-based materials (for example, 1 part, 2 parts, 3 parts, 4 parts or 5 parts), 80-100 parts of water (for example, 80 parts, 85 parts, 90 parts, 95 parts or 100 parts), and 1.2-1.8 parts of water reducer (for example, 1.2 parts, 1.4 parts, 1.6 parts, 1.7 parts or 1.8 parts).
[0041] Preferably, the cement mortar comprises the following components in parts by weight: 150 parts of cement, 150 parts of fly ash, 900 parts of river sand, 3 parts of the self-dispersing nano-silicon dioxide particles for cement-based materials, 90 parts of water and 1.5 parts of a water reducing agent.
[0042] The self-dispersible nano-silicon dioxide particles for cement-based materials of the present invention, as well as the preparation method and application thereof are described in detail below through specific examples.
[0043] In the following examples, the raw materials used can be purchased commercially; among them, the cement is P.O42.5 cement, and the fly ash is Class F fly ash.
[0044] Example 1
[0045] The method for preparing self-dispersible nano silicon dioxide particles for cement-based materials of this embodiment comprises the following steps:
[0046] 1) Silane (propyltrimethoxysilane) and nano-silicon dioxide (average size 50nm, SiO 2 The content is 99.5%), and the water is weighed at a mass ratio of 1.5:100, and the mass ratio of nano silicon dioxide: water is 10:100.
[0047] 2) Pour water into a container, then add silane into the water and start stirring and turning on the heating.
[0048] 3) When the water temperature rises to 80°C, add nano-silicon dioxide into the water and continue stirring.
[0049] 4) After 30 minutes of adding the nano-silica, the heating and stirring were stopped, the nano-silica was filtered out, and dried to obtain the self-dispersing nano-silica particles for cement-based materials of this embodiment.
[0050] The cement-based material (cement mortar) of this embodiment includes the following components in parts by mass: 150 parts of cement, 150 parts of fly ash, 900 parts of river sand, 3 parts of self-dispersing nano-silica particles for cement-based materials, 90 parts of water and 1.5 parts of polycarboxylate water reducer.
[0051] Example 2
[0052] The method for preparing self-dispersible nano silicon dioxide particles for cement-based materials of this embodiment comprises the following steps:
[0053] 1) Silane (a mixture of propyltriethoxysilane and dodecyltrimethoxysilane, the mass ratio of the two is 1:1) and nano-silicon dioxide (average size 80nm, SiO 2 The content is 99.2%), and the water is weighed at a mass ratio of 0.5:100, and the mass ratio of nano silicon dioxide: water is 5:100.
[0054] 2) Pour water into a container, then add silane into the water and start stirring and turning on the heating.
[0055] 3) When the water temperature rises to 90°C, add nano-silicon dioxide into the water and continue stirring.
[0056] 4) After 2 hours of adding the nano-silica, the heating and stirring were stopped, the nano-silica was filtered out, and dried to obtain the self-dispersing nano-silica particles for cement-based materials of this embodiment.
[0057] The cement-based material (cement mortar) of this embodiment: except that the self-dispersing nano-silica particles used for the cement-based material are different from those in Example 1 (that is, the self-dispersing nano-silica particles used for the cement-based material in Example 2 are used to replace the self-dispersing nano-silica particles used for the cement-based material in Example 1), the rest are consistent with Example 1.
[0058] Example 3
[0059] The method for preparing self-dispersible nano silicon dioxide particles for cement-based materials of this embodiment comprises the following steps:
[0060] 1) Silane (dodecyltriethoxysilane) and nano-silicon dioxide (average size 20nm, SiO 2 The content is 99.1%), and the water is weighed at a mass ratio of 1.5:100, and the mass ratio of nano silicon dioxide: water is 20:100.
[0061] 2) Pour water into a container, then add silane into the water and start stirring and turning on the heating.
[0062] 3) When the water temperature rises to 85°C, add nano-silicon dioxide into the water and continue stirring.
[0063] 4) After 2 hours of adding the nano-silica, the heating and stirring were stopped, the nano-silica was filtered out, and dried to obtain the self-dispersing nano-silica particles for cement-based materials of this embodiment.
[0064] The cement-based material (cement mortar) of this embodiment: except that the self-dispersing nano-silica particles used for the cement-based material are different from those in Example 1 (that is, the self-dispersing nano-silica particles used for the cement-based material in Example 3 are used to replace the self-dispersing nano-silica particles used for the cement-based material in Example 1), the rest are consistent with Example 1.
[0065] Example 4
[0066] The method for preparing self-dispersible nano silicon dioxide particles for cement-based materials of this embodiment comprises the following steps:
[0067] 1) Silane (dodecyltrimethoxysilane) and nano-silicon dioxide (average size 50nm, SiO 2 The content is 99.5%), and the water is weighed at a mass ratio of 0.5:100, and the mass ratio of nano-silicon dioxide: water is 20:100.
[0068] 2) Pour water into a container, then add silane into the water and start stirring and turning on the heating.
[0069] 3) When the water temperature rises to 95°C, add nano-silicon dioxide into the water and continue stirring.
[0070] 4) After 2 hours of adding the nano-silica, the heating and stirring were stopped, the nano-silica was filtered out, and dried to obtain the self-dispersing nano-silica particles for cement-based materials of this embodiment.
[0071] The cement-based material (cement mortar) of this embodiment: except that the self-dispersing nano-silica particles used for the cement-based material are different from those in Example 1 (that is, the self-dispersing nano-silica particles used for the cement-based material in Example 4 are used to replace the self-dispersing nano-silica particles used for the cement-based material in Example 1), the rest are consistent with Example 1.
[0072] Example 5
[0073] The method for preparing self-dispersible nano silicon dioxide particles for cement-based materials of this embodiment comprises the following steps:
[0074] 1) Silane (propyltrimethoxysilane) and nano-silicon dioxide (average size 80nm, SiO 2 The content is 99.2%), and the water is weighed at a mass ratio of 1.0:100, and the mass ratio of nano silicon dioxide: water is 8:100.
[0075] 2) Pour water into a container, then add silane into the water and start stirring and turning on the heating.
[0076] 3) When the water temperature rises to 95°C, add nano-silicon dioxide into the water and continue stirring.
[0077] 4) After 30 minutes of adding the nano-silica, the heating and stirring were stopped, the nano-silica was filtered out, and dried to obtain the self-dispersing nano-silica particles for cement-based materials of this embodiment.
[0078] The cement-based material (cement mortar) of this embodiment is consistent with Example 1 except that the self-dispersing nano-silica particles used for cement-based materials are different from those in Example 1 (that is, the self-dispersing nano-silica particles used for cement-based materials in Example 5 are used to replace the self-dispersing nano-silica particles used for cement-based materials in Example 1).
[0079] Example 6
[0080] The method for preparing self-dispersible nano silicon dioxide particles for cement-based materials of this embodiment comprises the following steps:
[0081] 1) Silane (a mixture of dodecylmethoxysilane and dodecylethoxysilane, with a mass ratio of 2:1) and nano-silicon dioxide (average size 20nm, SiO 2 The content is 99.1%), and the water is weighed at a mass ratio of nano-silicon dioxide: water = 15:100.
[0082] 2) Pour water into a container, then add silane into the water and start stirring and turning on the heating.
[0083] 3) When the water temperature rises to 95°C, add nano-silicon dioxide into the water and continue stirring.
[0084] 4) After 30 minutes of adding the nano-silica, the heating and stirring were stopped, the nano-silica was filtered out, and dried to obtain the self-dispersing nano-silica particles for cement-based materials of this embodiment.
[0085] The cement-based material (cement mortar) of this embodiment is consistent with Example 1 except that the self-dispersing nano-silica particles used for cement-based materials are different from those in Example 1 (that is, the self-dispersing nano-silica particles used for cement-based materials in Example 6 are used to replace the self-dispersing nano-silica particles used for cement-based materials in Example 1).
[0086] Example 7
[0087] The self-dispersed nano-silica particles for cement-based materials in this embodiment differ from those in Example 1 only in that the silane (propyltrimethoxysilane) and nano-silica (average size 50 nm, SiO 2 The content is 99.5%) and they are weighed at a mass ratio of 3:100; the rest are consistent with Example 1.
[0088] The cement-based material (cement mortar) of this embodiment is consistent with Example 1 except that the self-dispersing nano-silica particles used for cement-based materials are different from those in Example 1 (that is, the self-dispersing nano-silica particles used for cement-based materials in Example 7 are used to replace the self-dispersing nano-silica particles used for cement-based materials in Example 1).
[0089] Example 8
[0090] The self-dispersed nano-silica particles for cement-based materials in this embodiment differ from those in Example 6 only in that silane (a mixture of dodecylmethoxysilane and dodecylethoxysilane, with a mass ratio of 2:1) and nano-silica (average size 20 nm, SiO 2 The content is 99.1%) and they are weighed at a mass ratio of 0.3:100; the rest are consistent with Example 6.
[0091] The cement-based material (cement mortar) of this embodiment is consistent with Example 1 except that the self-dispersing nano-silica particles used for cement-based materials are different from those in Example 1 (that is, the self-dispersing nano-silica particles used for cement-based materials in Example 8 are used to replace the self-dispersing nano-silica particles used for cement-based materials in Example 1).
[0092] Example 9
[0093] The difference between this embodiment and embodiment 1 is that propyltriethoxysilane (PTOS) is used as silane, and the amounts of propyltriethoxysilane used are 0.5%, 1.0%, 1.5%, 2.0%, 3.0%, 5.0% and 7.0% respectively; the rest are consistent with embodiment 1.
[0094] Accordingly, the self-dispersing nano-silica particles for cement-based materials prepared in this example are abbreviated as NS-PTOS 0.5, NS-PTOS 1.0, NS-PTOS 1.5, NS-PTOS 2.0, NS-PTOS 3.0, NS-PTOS 5.0 and NS-PTOS 7.0, respectively.
[0095] The cement-based material (cement mortar) of this embodiment is consistent with Example 1 except that the self-dispersing nano-silica particles used for cement-based materials are different from those in Example 1 (that is, the self-dispersing nano-silica particles used for cement-based materials in Example 9 are used to replace the self-dispersing nano-silica particles used for cement-based materials in Example 1).
[0096] Example 10
[0097] The only difference between this embodiment and embodiment 1 is that: dodecyltrimethoxysilane (DTMS) is used as silane, and the amount of dodecyltrimethoxysilane (DTMS) used is 0.5%, 1.0%, 1.5%, 2.0%, 3.0%, 5.0% and 7.0%, respectively; in step 3), heating is stopped after the nano-silicon dioxide is added for 2 hours; the rest is consistent with embodiment 1.
[0098] Accordingly, the self-dispersible nano-silica particles for cement-based materials prepared in this example are abbreviated as NS-DTMS 0.5, NS-DTMS1.0, NS-DTMS1.5, NS-DTMS2.0, NS-DTMS 3.0, NS-DTMS 5.0 and NS-DTMS7.0, respectively.
[0099] The cement-based material (cement mortar) of this embodiment is consistent with Example 1 except that the self-dispersing nano-silica particles used for cement-based materials are different from those in Example 1 (that is, the self-dispersing nano-silica particles used for cement-based materials in Example 10 are used to replace the self-dispersing nano-silica particles used for cement-based materials in Example 1).
[0100] Comparative Example 1
[0101] The cement-based material (cement mortar) of this comparative example is different from that of Example 1 only in that: an average size of 50 nm and SiO 2 The nano silicon dioxide particles with a content of 99.5% replaced the self-dispersed nano silicon dioxide particles (abbreviated as NS) for cement-based materials in Example 1; the rest were consistent with Example 1.
[0102] Comparative Example 2
[0103] The cement-based material (cement mortar) of this comparative example is different from that of Example 2 in that: an average size of 80 nm and SiO 2 The nano-silicon dioxide particles with a content of 99.2% replace the self-dispersing nano-silicon dioxide particles for cement-based materials in Example 2; the rest are consistent with Example 2.
[0104] Comparative Example 3
[0105] The cement-based material (cement mortar) of this comparative example is different from that of Example 3 only in that: an average size of 20 nm and SiO 2 The nano-silicon dioxide particles with a content of 99.1% replace the self-dispersing nano-silicon dioxide particles for cement-based materials in Example 3; the rest are consistent with Example 3.
[0106] Comparative Example 4
[0107] The cement-based material (cement mortar) of this comparative example is different from that of Example 4 only in that: an average size of 50 nm and SiO 2 The nano-silicon dioxide particles with a content of 99.5% replace the self-dispersing nano-silicon dioxide particles for cement-based materials in Example 4; the rest are consistent with Example 4.
[0108] Comparative Example 5
[0109] The cement-based material (cement mortar) of this comparative example is different from that of Example 5 only in that: an average size of 80 nm and SiO 2 The nano-silicon dioxide particles with a content of 99.2% replace the self-dispersing nano-silicon dioxide particles for cement-based materials in Example 5; the rest are consistent with Example 5.
[0110] Comparative Example 6
[0111] The cement-based material (cement mortar) of this comparative example is different from that of Example 6 in that: 2 The nano-silicon dioxide particles with a content of 99.1% replace the self-dispersing nano-silicon dioxide particles for cement-based materials in Example 6; the rest are consistent with Example 6.
[0112] Comparative Example 7
[0113] The cement-based material (cement mortar) of this comparative example is different from that of Example 1 only in that the self-dispersed nano-silicon dioxide particles (abbreviated as Plain) used for the cement-based material are omitted; the rest are consistent with Example 1.
[0114] Experimental example
[0115] According to "Cement-based Self-leveling Mortar for Floor" (JC / T 985-2017) and "Test Method for Strength of Cement Mortar" (GB / T 17671-2021), the cement mortars of the above-mentioned Examples 1-8 and Comparative Examples 1-6 were subjected to performance tests, and the test results of relevant performance indicators are shown in Table 1 below.
[0116] Table 1 Cement mortar fluidity and strength test results
[0117]
[0118]
[0119] The test results of the fluidity of the cement mortars of Examples 9-10, Comparative Example 1 and Comparative Example 7 are as follows: Figure 3 As shown; the test results of the compressive strength of the cement mortar of Example 9, Comparative Example 1 and Comparative Example 7 are as shown Figure 4 As shown; the test results of the compressive strength of the cement mortar of Example 10, Comparative Example 1 and Comparative Example 7 are as shown Figure 5 shown. Figure 3-5 The test results are shown in Table 2 below. PTOS is propyltriethoxysilane, DTMS is dodecyltrimethoxysilane, NS stands for nanosilica, the silane name stands for the silane used for modification, and the number behind it stands for the mass percentage of silane adsorption.
[0120] Table 2
[0121]
[0122]
[0123] Depend on Figure 3 It can be seen that the fluidity of the control group mortar (Plain group) without NS particles is 90mm. After adding 1% unmodified NS particles, the fluidity of the mortar dropped significantly, only 51mm. The modification of PTOS and DTMS improved the fluidity of the mortar mixed with NS particles. When the adsorption amount was below 2.0%, the fluidity of the mortar basically increased linearly with the increase of silane adsorption, and was close to the control group mortar. When the silane adsorption amount was 2.0-5.0%, the fluidity of the mortar mixed with DTMS modified NS particles remained almost unchanged, while the fluidity of the mortar mixed with PTOS modified NS particles increased slightly. When the silane adsorption amount exceeded 5.0%, the fluidity of the mortar mixed with both silane modified NS particles increased, and exceeded the control group mortar at a certain adsorption amount. In addition, at the same mass adsorption amount, the fluidity of the mortar mixed with POTS modified NS particles is smaller than that of the mortar mixed with DTMS modified NS particles, but the difference is not large.
[0124] Depend on Figure 4 It can be seen from the figure that the unmodified NS particles can not only improve the compressive strength at early ages (1d, 3d), but also improve the compressive strength at 7d and 28d. For PTOS-modified NS particles, at lower adsorption amounts (0.5% and 1.0%), NS particles improve the compressive strength of mortar at 1d, 3d, 7d, and 28d. However, as the adsorption amount continues to increase (greater than 1.5%), the compressive strength is lower than that of the mortar with unmodified NS particles.
[0125] Depend on Figure 5 It can be seen that the effect of DTMS adsorption on the compressive strength of mortar also shows the same Figure 4 The difference is that when the DTMS adsorption amount is less than 1.5%, the NS particles increase the compressive strength of the mortar, while when it exceeds 2.0%, the compressive strength of the mortar is reduced.
[0126] In summary:
[0127] 1. The hydroxyl groups generated by hydrolysis of the silane in the technical solution of the present invention react with the hydroxyl groups on the surface of the nano-silicon dioxide (such as Figure 1-2 ), and thus adsorbed to the surface of nano-silicon dioxide particles by chemical adsorption. Its adsorption force is more stable than the physical adsorption of surfactants, so the dispersion effect is more stable. In addition, the silane carbon chain has a steric hindrance, so its dispersion effect is good.
[0128] 2. In the technical solution of the present invention, the steric hindrance of the silane carbon chain is used to disperse the nano-silica particles, and the hydrophobicity of silane is used to reduce the water adsorption on the surface of the nano-particles, thereby greatly reducing the influence of the nano-silica particles on the working performance of cement-based materials.
[0129] 3. The technical solution of the present invention selects alkyl silane as a modifier to avoid the retarding effect of active groups on the silane carbon chain, such as amino, epoxy, acyloxy, etc., on cement hydration.
[0130] 4. In the technical solution of the present invention, the adsorption amount of silane on the surface of nano-silica particles is limited to less than 1.5%, which reduces the hydrophobicity of silane on the nano-silica and Ca(OH) 2 The inhibition of the pozzolanic reaction between cement and cementitious materials avoids the decrease in the strength of cement-based materials after 28 days.
[0131] 5. The present invention directly adsorbs silane onto the surface of nano-silicon dioxide particles, so the preparation process is simple, the adsorption amount is small, the cost is low, and it is easier to promote and apply.
[0132] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing self-dispersible nano-silicon dioxide particles for cement-based materials, characterized in that: The steps include: (1) mixing alkylsilane and water, stirring and heating; (2) When the temperature is heated to above 80°C, add nano-silicon dioxide and continue stirring; (3) After the stirring is completed, the solid and liquid are separated and dried to obtain the self-dispersing nano-silicon dioxide particles for cement-based materials.
2. The method for preparing self-dispersible nano-silicon dioxide particles for cement-based materials according to claim 1, characterized in that: The mass ratio of the alkylsilane to the nano-silicon dioxide is (0.5-1.5):
100.
3. The method for preparing self-dispersible nano-silicon dioxide particles for cement-based materials according to claim 1, characterized in that: The silane is at least one of propyltrimethoxysilane, propyltriethoxysilane, dodecyltrimethoxysilane and dodecyltriethoxysilane.
4. The method for preparing self-dispersible nano-silicon dioxide particles for cement-based materials according to claim 3, characterized in that: The alkylsilane includes dodecyltrimethoxysilane and / or dodecyltriethoxysilane. After adding the nano-silica in step (2), stirring is continued for 2 hours and then heating and stirring are stopped.
5. The method for preparing self-dispersible nano-silicon dioxide particles for cement-based materials according to claim 3, characterized in that: The alkyl silane is propyltrimethoxysilane and / or propyltriethoxysilane. After adding the nano-silica in step (2), stirring is continued for 30 minutes and then heating or stirring is stopped.
6. The method for preparing self-dispersible nano-silicon dioxide particles for cement-based materials according to claim 1, characterized in that: The average size of the nano-silicon dioxide is less than 100nm, and the SiO2 content is greater than 99%; The mass ratio of the nano silicon dioxide to water is (5-20):
100.
7. A self-dispersing nano-silicon dioxide particle for cement-based materials, characterized in that: The self-dispersing nano silicon dioxide particles for cement-based materials are prepared by the method according to any one of claims 1 to 6.
8. A cement-based material, characterized in that: The component of the cement-based material includes the self-dispersing nano-silica particles for cement-based materials as claimed in claim 7.
9. The cement-based material according to claim 8, characterized in that The cement-based material is cement mortar, and the cement mortar comprises the following components in parts by weight: 140-160 parts of cement, 140-160 parts of fly ash, 850-950 parts of river sand, 1-5 parts of the self-dispersing nano silicon dioxide particles for cement-based materials, 80-90 parts of water and 1.2-1.8 parts of a water reducing agent.